Effects of physical activity on earnings in the Brazilian labor market - Marcia Regina Godoy; Divanildo Triches (EconomiA, 2017)
This article investigates the effects of physical activity on earnings in the Brazilian labor market, analyzing workers aged between 30 and 50 years. To that end, quantile regression was applied to analyze microdata from the 2008 National Household Sample Survey (PNAD). The results showed that workers who engage in regular physical exercise exhibit better social and economic conditions compared to sedentary individuals. Sedentary lifestyles are typically more common among female employees than their male counterparts and this is reflected in earnings in the labor market. The impact of physical activity on wages varied from 15.0 to 31.0% and was greater among the highest quantiles. The lowest salaries were recorded among non-white sedentary women.
Keywords: 330; Physical activity; Earnings; Labor market; Health